Growth And Yield Of Lettuce (Lactuca sativa L.) Under Organic Cultivation - Mujiono, Mujiono; Suyono, Suyono; Purwanto, Purwanto (Universitas Muhammadiyah Yogyakarta, 2017)
This research was aimed to know selected assemblies of technology in organic lettuce cultivation based on liquid organic fertilizer and selected botanical pesticide. It used a Complete Randomized design (CRD) with two treatments and 16 replicates. The treatments were P1 (goat manure + SO-Kontan LQ soil Liquid Organic Fertilizer (LOF) (6 ml/l) + combined SO-Kontan Fert leaf LOF (6 ml/l) + maja-gadung botanical pesticide (6%) + biological agent Trichoderma harzianum (10 g/plant) and P2 (goat manure + SO-Kontan LQ soil LOF Lq (6 ml/l) + combined SO-Kontan Fert leaf LOF (6 ml/l) + maja-gadung botanical pesticide (6%) + bamboo leaves + biological agent Trichoderma harzianum (10 g/plant). Results of the research performed that the P2 assembly was more superior than P1 for all variables of growth and yield, except the green color of leaves. The technology assembly in the organic lettuce cultivation based on LOF and selected botanical pesticide was the P2 (goat manure + SO-Kontan LQ soil LOF Lq (6 ml/l) + combined SO-Kontan Fert leaf LOF (6 ml/l) + maja-gadung botanical pesticide (6%) + bamboo leaves + biological agent of Trichoderma harzianum (10 g/polybag) resulted in the productivity of 87.17 g per plant.